2021
DOI: 10.1186/s13041-021-00766-x
|View full text |Cite
|
Sign up to set email alerts
|

The Ser19Stop single nucleotide polymorphism (SNP) of human PHYHIPL affects the cerebellum in mice

Abstract: The HapMap Project is a major international research effort to construct a resource to facilitate the discovery of relationships between human genetic variations and health and disease. The Ser19Stop single nucleotide polymorphism (SNP) of human phytanoyl-CoA hydroxylase-interacting protein-like (PHYHIPL) gene was detected in HapMap project and registered in the dbSNP. PHYHIPL gene expression is altered in global ischemia and glioblastoma multiforme. However, the function of PHYHIPL is unknown. We generated PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…S15E ). Although the exact function of the gene PHYHIPL in the human brain is not fully understood, studies have suggested its potential association with cerebellum-related disorders in mice (45). Therefore, further understanding of the transcriptional regulation of this gene is meaningful for subsequent research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S15E ). Although the exact function of the gene PHYHIPL in the human brain is not fully understood, studies have suggested its potential association with cerebellum-related disorders in mice (45). Therefore, further understanding of the transcriptional regulation of this gene is meaningful for subsequent research.…”
Section: Resultsmentioning
confidence: 99%
“…S15E). Although the exact function of the gene PHYHIPL in the human brain is not fully understood, studies have suggested its potential association with cerebellum-related disorders in mice (45).…”
Section: Deciphering Tads In the Very Noisy And Sparse Contact Maps O...mentioning
confidence: 99%
“…Pkd1l1 participates in regulating ciliary drive during development, and plays a key role in establishing left-right asymmetry in vertebrates (Field et al 2011). Phyhipl affects the morphology and signal transduction of Purkinje cells (PC) in cerebellum, which is related to the motor learning ability of organisms (Sugimoto et al 2021). sp8b takes part in the Wnt signaling pathway and affects neural posteriorization during the neural development stage (Mohanty 2017).…”
Section: Discussionmentioning
confidence: 99%